PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY0LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAHaMATEMATIS PESERTA DIDIK KELAS IX SMPaNEGERI 6 KOTA SOLOK - Fadhli Ilham (Jurnal Edukasi dan Penelitian Matematika, 2021)
this study aims0to determine and describe0whether0the0mathematical0problem0solving ability of students0who learn with the discovery learning model is better0than0students0who learn with the direct learning model in class IX SMP Negeri 6 Solok City. The type of the reseach is a quasy-experimental re-seach with a design that is static group design. The0population0of0this0study0was0class0IX at SMP Negeri 6 Solok City with the reseach sample being IX.3 as0the0experimental0class and IX.4 as the control class. The sampling0technique0used0is0sample0random0sampling, where0each0member0of0the population has the0same0opportunity0to be a sample. The reseach instrument used is the final test of0mathematical problem0solving. Based on the results of the final test hypothesis, the P-Value = 0,014, meaning that the P-Value0is smaller than 0,05, which means rejecting H0. Then, after analyzing the0results of the final problem0solving test, the0average0value of experimental class was higher than the average value of the control class. This it can be concluded that the mathematical0problem0solving0ability0of0students0who0learn0to0use the discovery learning model is0better0than0students who learn to use directilearning in class IX of SMP Negeri 6 Solok City. Keywords–Discovery0Learning, kemampuan0pemecahan0masalah, pembelajaran langsung.